Resilience mediates the prediction of alienation towards parents on subjective well-being in rural left-behind children: a 12-month longitudinal study - Zhang, Mengjia; Sun, Xiaoxiao; Cui, Chun; Tan, Jieying; Ren, Xiaomei; Dai, Qin (Frontiers in Psychiatry, 2024)
Objective: Parent-child relationship is critical for children’s well-being. In China, the large number of left-behind children (LBC, one or both parents leaving for work for at least 6 months) raises public concern. Although LBC often report poor mental health status and higher alienation towards parents, the dynamic trend of subjective well-being in this population, as well as the prediction of alienation towards parents on LBC’s subjective well-being, remain unrevealed. This study aimed to examine the dynamic trend of subjective well-being in Chinese LBC and further explore the predictional influence of alienation towards parents, with resilience as a potential mediator. Methods: We recruited 916 rural LBC in China and investigated them at five waves (baseline, and 1, 3, 6, and 12 months later) using Inventory of Alienation towards Parents (IAP), Resilience Scale for Chinese Adolescents (RSCA) and Subjective Happiness Scale (SHS). We used hierarchical linear modeling (HLM) for analysis. Results: At baseline, no significant differences were found in the scores of alienation towards parents, resilience, and subjective well-being on gender, grade, or type of LBC. A significant correlation existed between the scores of alienation towards parents, resilience, and subjective well-being. HLM showed a linear increase in the subjective well-being of rural LBC. Alienation toward both mother and father negatively predicted the developmental trajectory of children’s subjective well-being over 12 months. Moreover, resilience partially mediated this prediction. Conclusion: This study is among the first to reveal that alienation towards parents predicts the developmental trajectory of later LBC’s subjective well-being, with resilience as a mediator. These findings warrant the necessity of paying attention to alienation toward parents to ensure the mental health of LBC, giving valuable guidance to parents, schools and governments.